Mapping the evolutionary landscape of Zika virus infection in immunocompromised mice. Issue 2 (11th December 2020) - Johnson, Katherine E E; Noval, Maria G; Rangel, Margarita V; De Jesus, Elfie; Geber, Adam; Schuster, Samantha; Cadwell, Ken; Ghedin, Elodie; Stapleford, Kenneth A
Abstract: The fundamental basis of how arboviruses evolve in nature and what regulates the adaptive process remain unclear. To address this problem, we established a Zika virus (ZIKV) vector-borne transmission system in immunocompromised mice to study the evolutionary characteristics of ZIKV infection. Using this system, we defined factors that influence the evolutionary landscape of ZIKV infection and show that transmission route and specific organ microenvironments impact viral diversity and defective viral genome production. In addition, we identified in mice the emergence of ZIKV mutants previously seen in natural infections, including variants present in currently circulating Asian and American strains, as well as mutations unique to the mouse infections. With these studies, we have established an insect-to-mouse transmission model to study ZIKV evolution in vivo . We also defined how organ microenvironments and infection route impact the ZIKV evolutionary landscape, providing a deeper understanding of the factors that regulate arbovirus evolution and emergence.